2008
DOI: 10.1111/j.1567-1364.2007.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the yeast transcriptome during wine fermentation reveals a novel fermentation stress response

Abstract: In this study, genome-wide expression analyses were used to study the response of Saccharomyces cerevisiae to stress throughout a 15-day wine fermentation. Forty per cent of the yeast genome significantly changed expression levels to mediate long-term adaptation to fermenting grape must. Among the genes that changed expression levels, a group of 223 genes was identified, which was designated as fermentation stress response (FSR) genes that were dramatically induced at various points during fermentation. FSR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 60 publications
14
182
0
Order By: Relevance
“…However, HSP104 expression was highest in the FF stage at 13°C in this study. These results suggested that HSP104 expression was probably induced by ethanol stress or cold stress (Marks et al 2008).…”
Section: Discussionmentioning
confidence: 57%
“…However, HSP104 expression was highest in the FF stage at 13°C in this study. These results suggested that HSP104 expression was probably induced by ethanol stress or cold stress (Marks et al 2008).…”
Section: Discussionmentioning
confidence: 57%
“…response to various stress conditions (Gasch et al, 2000) and during the alcoholic fermentation process (Rossignol et al, 2003;Marks et al, 2008). However, this gene was poorly characterized, despite the presence of a clear C 2 H 2 zinc finger DNA-binding motif.…”
Section: (A) (B)mentioning
confidence: 99%
“…Previous microarray analysis of fermenting grape juice revealed the increased transcription of YPL230w (Rossignol et al, 2003;Marks et al, 2008). We analysed the transcription of NSF1 in response to different carbon conditions by growing the wild-type strain to early exponential phase in rich media with glucose (YPD), acetate (YPA), ethanol (YPE) or glycerol (YPGlyc) as carbon source.…”
Section: Nsf1 Expression Is Activated By Non-fermentable Carbon Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transcriptomic studies have also been published for research conducted with wine yeast strains (Erasmus et al, 2003;Rossignol et al, 2003;Varela et al, 2005;Mendes-Ferreira et al, 2007;Marks et al, 2008;Pizarro et al, 2008;Rossouw & Bauer, 2008). These studies have illuminated the intrinsic genetic and regulatory mechanisms involved in fermentation, and have greatly increased our understanding of this important process.…”
Section: -Transcriptomicsmentioning
confidence: 99%